2023
DOI: 10.1038/s41598-023-40564-0
|View full text |Cite
|
Sign up to set email alerts
|

Land use and land cover (LULC) performance modeling using machine learning algorithms: a case study of the city of Melbourne, Australia

Jagannath Aryal,
Chiranjibi Sitaula,
Alejandro C. Frery

Abstract: Accurate spatial information on Land use and land cover (LULC) plays a crucial role in city planning. A widely used method of obtaining accurate LULC maps is a classification of the categories, which is one of the challenging problems. Attempts have been made considering spectral (Sp), statistical (St), and index-based (Ind) features in developing LULC maps for city planning. However, no work has been reported to automate LULC performance modeling for their robustness with machine learning (ML) algorithms. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Classification of space images is a rather complex process, the methodology of which is constantly being improved [93][94][95], and the division into the number of classes depends on the predictors that prevail in the space under study [96,97]. Considering the results of these studies, we used one of the most reliable and, therefore, widely used algorithms-Random Forest-to classify Landsat satellite images.…”
Section: Discussionmentioning
confidence: 99%
“…Classification of space images is a rather complex process, the methodology of which is constantly being improved [93][94][95], and the division into the number of classes depends on the predictors that prevail in the space under study [96,97]. Considering the results of these studies, we used one of the most reliable and, therefore, widely used algorithms-Random Forest-to classify Landsat satellite images.…”
Section: Discussionmentioning
confidence: 99%
“…The results underline the complex interplay between urban development and environmental changes in the region. In this regard, Aryal et al [48] indicated that the results could vary depending on the geographical characteristics of the study area. Although several factors influence urbanization, one of those detected in our research is migration, which played a crucial role in determining the Gelephu's LULC dynamics.…”
Section: Ndvi Change Detection and Statisticsmentioning
confidence: 99%
“…6). Comparing these data points with the study area's current LULC facilitates the validation of the classi ed results (Aryal et al 2023). The confusion matrix is critical in analyzing key metrics based on reference or ground truth data, such as overall accuracy, producer accuracy, user accuracy, and the Kappa Coe cient of the classi ed maps.…”
Section: Post-classi Cationmentioning
confidence: 99%